Solar-to-fuels conversion over In2O3/g-C3N4 hybrid photocatalysts - Liao, Yusen (2013)
We have achieved in-situ growth of In2O3 nanocrystals onto the sheet-like g-C3N4 surface. The resulting In2O3-g-C3N4 hybrid structures exhibit considerable improvement on the photocatalytic activities for H2 generation and CO2 reduction. The enhanced activities are attributed to the interfacial transfer of photogenerated electrons and holes between g-C3N4 and In2O3, leading to effective charge separation on both parts. Further studies by transient PL spectroscopy confirm that the In2O3-g-C3N4 heterojunctions remarkably promote the charge transfer efficiency, thereby increase the charge carrier lifetime for the photocatalytic reactions.